Stereoselective synthesis of spiroannulated cyclopentenones by the Pauson-Khand reaction on carbohydrate derived enynes - Hotha, Srinivas; Maurya, S. K.; Gurjar, M. K. (Tetrahedron Letters, 2005)
The stereoselective synthesis of spiroannulated cyclopentenones by the Pauson-Khand reactions on hexose and pentose derived enynes was achieved under carbon monoxide free conditions using a stoichiometric quantity of Co-2(CO)(8). The cobalt complex of the alkyne was cleaved using dimethoxyethane-acetonitrile at 85 degrees C to furnish spiroarmulated cyclopentenones in 75-94% yields. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; cyclopentenone; diversity oriented synthesis; Pauson-Khand reaction